2002
DOI: 10.1161/01.hyp.0000015613.78314.9e
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Improves Left Ventricular Diastolic Function Under Long-Term Angiotensin-Converting Enzyme Inhibition in Heart Failure

Abstract: Abstract-Both systolic and diastolic cardiac dysfunction coexist in various degrees in the majority of patients with heart failure. Although ACE inhibitors are useful in the treatment of heart failure, the roles of bradykinin in the systolic and diastolic properties of left ventricular function under long-term treatment of ACE inhibitor have not been fully elucidated. We therefore evaluated the changes in left ventricular function, histomorphometry, and the expression of several failing heart related genes, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…21 Real-time PCR was performed with a LightCycler (Roche Molecular Biochemicals, Mannheim, Germany) using a commercially available mix containing Taq DNA polymerase, SYBR-Green I, and deoxyribonucleoside triphosphates (FastStart DNA Master SYBR Green I kit; Roche). Canine glutaraldehyde-3-phosphate dehydrogenase (GAPDH) and eNOS specific primer pairs were synthesized according to the published data.…”
Section: Quantification Of Nox4 Gp91phox P47phox and P22phox (Nadphmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Real-time PCR was performed with a LightCycler (Roche Molecular Biochemicals, Mannheim, Germany) using a commercially available mix containing Taq DNA polymerase, SYBR-Green I, and deoxyribonucleoside triphosphates (FastStart DNA Master SYBR Green I kit; Roche). Canine glutaraldehyde-3-phosphate dehydrogenase (GAPDH) and eNOS specific primer pairs were synthesized according to the published data.…”
Section: Quantification Of Nox4 Gp91phox P47phox and P22phox (Nadphmentioning
confidence: 99%
“…Canine glutaraldehyde-3-phosphate dehydrogenase (GAPDH) and eNOS specific primer pairs were synthesized according to the published data. 21 Putative canine PCR primers for Nox4, gp91phox, p47phox and p22phox genes were designed based on homology with the highly conserved regions of the coding sequence of the human genes (gene bank: AF254621, BC032720, AF330627, NM000101). The canine Nox4, gp91phox, p47phox and p22phox-specific primer pairs were as follows.…”
Section: Quantification Of Nox4 Gp91phox P47phox and P22phox (Nadphmentioning
confidence: 99%
“…Third, it has been shown that ACE inhibitors exert a BK-mediated favorable effect on LV diastolic function. 18 Thus, one mechanism by which BK exerts its protective effect on myocardial contractile function may be related to its effects on LV diastolic function. In agreement with previous reports, 15,16 this study showed a rightward shift of LV diastolic pressure-diameter curve, with an unchanged LV chamber stiffness after 3 weeks of pacing in vehicle-treated dogs.…”
Section: Tonduangu Et Al Chronic Effects Of Bradykinin In Heart Failurementioning
confidence: 99%
“…This result seems to be in the same line as recent reports showing that chronic treatment with quinapril enhanced eNOS protein expression through a BK-dependent mechanism in normal rats 23 and that chronic treatment with enalapril preserved eNOS mRNA level, which was attenuated by concomitant BK B2 receptor antagonist in the pacinginduced HF. 18 The preserved eNOS expression could maintain NO production. By limiting afterload increase and by inhibiting myocardial mitochondrial respiration, 17,24 NO may have attenuated myocardial O 2 consumption during rapid pacing.…”
Section: Tonduangu Et Al Chronic Effects Of Bradykinin In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation